代际财富传承视角下城中村女性土地权维护动因研究——以中国广西南宁市两个城中村为例 - Yuan Xu (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
From the intergenerational wealth transfer perspective, this study explores motivations and practical significance of women’s land rights protection in Nanning’s (Guangxi, China) urban villages. Empirical research on Xingxing and Guanguan Villages shows traditional gender norms and institutional exclusion in village rules restrict married women’s land inheritance rights. Besides,